2001
DOI: 10.1007/pl00004039
|View full text |Cite
|
Sign up to set email alerts
|

Vault Prolapse II: Restoration of Dynamic Vaginal Supports by Infracoccygeal Sacropexy, an Axial Day-Case Vaginal Procedure

Abstract: Our objective was to present and critically analyze the first 75 infracoccygeal sacropexy (ICS) operations for cure of vault prolapse. Level 1 reconstruction was achieved by the insertion of a tension-free vaginal tape (nylon) via the ischiorectal fossa into a transversely incised posterior vaginal fornix. Level 2 defects were repaired by cutting a central 'bridge' in the posterior vaginal wall and suturing the lateral flaps to the bridge. Level 3 repair reconstituted the perineal body. Postoperative pain was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
108
1
19

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(132 citation statements)
references
References 10 publications
4
108
1
19
Order By: Relevance
“…Previous studies have reported a high concomitant cure rate for bladder symptoms [2]. This study confirms previous reports of high rates of improvement in symptoms of prolapse, urgency, nocturia, pelvic pain, and difficulty voiding [6]. In our case series, the cure rates were We also compared the cure rates between the two groups of vault and uterovaginal prolapse ( Table 4).…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies have reported a high concomitant cure rate for bladder symptoms [2]. This study confirms previous reports of high rates of improvement in symptoms of prolapse, urgency, nocturia, pelvic pain, and difficulty voiding [6]. In our case series, the cure rates were We also compared the cure rates between the two groups of vault and uterovaginal prolapse ( Table 4).…”
Section: Discussionsupporting
confidence: 88%
“…In none of the studies were complications separately described for the subgroup of women in which the uterus was preserved. Therefore, for describing complications, we used data for women who underwent a posterior intravaginal slingplasty with and without preservation of the uterus [37][38][39][40][41][42][43][44][45][46][47].…”
Section: Study Selectionmentioning
confidence: 99%
“…In 2001, the posterior intravaginal slingplasty was introduced by Petros [41]. It was a minimally invasive, transperineal technique providing Level I support, as described by DeLancey, by making neo-sacrouterine ligaments using mesh [53].…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…The first kit, the posterior intravaginal slingplasty (PIVS; U.S. Surgical, Tyco Healthcare Group, Norwalk, CT), achieved Level I support by tunneling a nylon tape through the ischiorectal fossa into an incision in the posterior vaginal fornix. [28] The tunnelers exited through the iliococcygeus muscle near the ischial spines, and the deployed tape was sutured to the vaginal vault. After more than four years of follow-up, an apical recurrence was reported in only 6%, but mesh extrusion was observed in 5.3% and two intraoperative rectal perforations were reported.…”
Section: Interposition Grafts For Pop Repairmentioning
confidence: 99%